Analisis Pengawasan Sistem Retribusi Parkir Oleh Dinas Perhubungan Dan Transportasi DKI Jakarta ( Studi Kasus : Pungutan Liar Oleh Juru Parkir Di Pasar Johar Baru ) - Prasetiyani, Erni; Kusuma Atmaja, Anita (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Governor's Regulation Number 31 of 2017 concerning Parking Service Tariffs states that for two-wheeled vehicles, the tariff is Rp 2,000 to Rp 3,000, for four-wheeled vehicles Rp 3,000 to Rp 5,000. But the reality is that there are still parking attendants who collect parking service levies that are not in accordance with the regulations. The purpose of this study is to find out the supervision process and obstacles from the Parking Management Unit of the Central Jakarta City Transportation Office, especially the Johar Baru Market, on the parking service levy on the side of the Johar Baru City Public Road. This study uses the supervision theory by Robbins and Coulter. This study uses a research method with a qualitative descriptive approach. The results of the study show that the main focus of supervision carried out by the Parking Management Unit of the Central Jakarta City Transportation Agency is to minimize illegal parking attendants and routine coaching to parking attendants on duty at Johar Baru Market. The lack of supervision of the collection of parking service levies by the Central Jakarta City Transportation Office causes there are still parking attendants who collect in accordance with regulations. There are several obstacles to the Parking Management Unit of the Central Jakarta City Transportation Agency in carrying out the supervision process of parking service levies, namely complaints from the public, fare withdrawals not in accordance with the provisions, service understanding, and ticket use.